Analisis Teknik Dasar Sepak Sila Olahraga Sepak Takraw Atlet PSTI Kota Lubuklinggau - Makhril Makhril; Wawan Syahfutra; Hengky Remora (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
This study aims to describe the basic techniques of pencak silat at PSTI athletes in Lubuklinggau. This research is a type of qualitative descriptive research. The subjects of this study were the trainers and students of the PSTI pencak silat, Lubuklinggau city. Data collection techniques were conducted by interview, observation, and documentation. Data were analyzed using components recommended by Miles and Huberman. Data collection was carried out in the afternoon after the data collected were immediately analyzed. The results showed that the value of the movement in the basic technique of Silat was seen when the researchers made observations. The study of the basic technique of limb attacks describes the total number of 7 students who have been observed one by one and are said to be able to perform basic techniques of silage, serve and smash correctly and appropriately. That the results of this study indicate that in carrying out the precepts of PSTI the city of Lubuklinggau is categorized as good. Keywords: Research and Development, Soccer, Sepak Takraw.